Therapeutic and subsidiarity principles: an approach to the humanizing character of the Bioethics Ecuadorian Society - Rolando Medina Peña; Guido Estuardo Coronel Núñez; Maigre Gallo González; Diana Elisa Palmero Urquiza (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2019)
The principles of personalist bioethics are of crucial importance in the human dignity preservation and understanding. The principle of totality or therapeutic, and that of sociability and subsidiarity, are the object of reflection in this study, as well as the way in which they are manifested through the Ecuadorian Society of Bioethics, through the analytical and conceptual foundation on the origin and consistency of these. For this, documentary review, analysis and synthesis were used. These reflections allow us to confirm that the Bioethics Ecuadorian Society is an example of the need to base, in civil society, the protection of human dignity, and the use of such science as a normative and educational instrument; and that the subject is a social being and needs socialization, so as to help and contribute to mutual improvement. Consequently and as an indissoluble part, we find subsidiarity, in which certain social institutions play their roles.